Hematopoietic Stem Cell Development - Godin, Isabelle; Cumano, Ana (Medical Intelligence Unit, 2006)
Hematopoietic Stem Cells brings together articles covering the biology of hematopoietic stem cells during embryonic development, reporting particular aspects of fly, fish, avian and mammalian models. Thus, this book allows a comparative overview of hematopoietic stem cell generation in the different classes, emphasizing the conserved trends in development. This book culminates with state-of -the art knowledge on hematopoietic development in human species and discussions of the most recent breakthroughs with relevance to both researchers and clinicians.